Incidental detection of sinus mucosal abnormalities on CT and MRI imaging of the head - Nazri, Mohammad (AME Publishing Company, 2013)
PURPOSE: To investigate the prevalence of incidental sinus abnormalities on CT and MRI imaging of the head, and identify if there is any correlation between patient symptomatology and image findings. MATERIALS AND METHODS: One hundred and fifteen patients who underwent head CT or MRI for  non-sinus related indications were included in this study, with image findings being analysed based on the Lund-Mackay Grading System (LMS). These were compared with their symptomatology based on the SNAQ-11 questionnaire. Two reviewers who were blinded to the patients’ SNAQ-11 scores analysed the images. Patients were also referred to an ENT surgeon for anterior rhinoscopy in an attempt to seek a correlation between symptomatology and/or imaging findings against clinical assessment. RESULTS: The prevalence of incidental sinus abnormalities is between 14.8% and 37% for CT and 29.5% and 85.2% for MRI, depending upon the cutoff LMS used. There was no significant difference in the incidence rate between the different age groups or genders. Asymptomatic patients had a significantly lower incidence rate of sinus mucosal abnormalities (8.2-57.1%) when compared to the symptomatic patients (33.3-66.7%) (P<0.01). A significant correlation was found between the MRI sinus findings and patients’ symptoms (r=0.59, P<0.001) with no correlation demonstrated in the CT group. The mean LM score for the patients with clinical sinusitis was 6.2, while the normal patients had a mean LM score of 2.2. CONCLUSIONS: MRI is more sensitive than CT to detect sinus mucosal abnormalities. A significant correlation is noticed between MRI findings and patients’ symptomatology.